2008
DOI: 10.1037/0012-1649.44.4.1095
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and child contributions to cortisol response to emotional arousal in young children from low-income, rural communities.

Abstract: Relations of maternal and child characteristics to child cortisol reactivity to and recovery from emotional arousal were examined prospectively at approximately 7 months of age (infancy) and then again at approximately 15 months of age (toddlerhood). The sample was diverse and population based (N = 1,292 mother-infant dyads) and included families from predominantly low-income, rural communities. Maternal behavior, family income-to-need ratio and social advantage, and child temperament, attention, and mental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
139
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 162 publications
(168 citation statements)
references
References 74 publications
25
139
3
1
Order By: Relevance
“…Recent advances in neuroscience suggest that poverty-related gaps in achievement are accompanied by poverty-related differences in brain structure and function [2][4] and differences in the regulation of attention, emotion, stress response physiology, and executive functions important for early learning [5], [6]. These findings support the hypothesis that SES-related gaps in academic abilities at school entry are in part attributable to effects of poverty on children’s self-regulation development [7][9].…”
Section: Introductionsupporting
confidence: 57%
“…Recent advances in neuroscience suggest that poverty-related gaps in achievement are accompanied by poverty-related differences in brain structure and function [2][4] and differences in the regulation of attention, emotion, stress response physiology, and executive functions important for early learning [5], [6]. These findings support the hypothesis that SES-related gaps in academic abilities at school entry are in part attributable to effects of poverty on children’s self-regulation development [7][9].…”
Section: Introductionsupporting
confidence: 57%
“…Findings from this sample have also shown that sensitive parenting behavior observed when children are infants is associated with a higher level of cortisol reactivity to an emotionally arousing situation when children are 7 months old and with an overall lower level of cortisol in response to emotional arousal when children are 15 months old (Blair et al, 2008). Findings from that previous analysis also indicated that child temperament, namely distress to novelty, was associated with a higher level of cortisol at age 15 months.…”
mentioning
confidence: 74%
“…Socioeconomic status also shows influence on motivation, attention, and cognitive control (e.g., Blair et al, 2008;Pilgrim, Marin, & Lupien, 2010), which may have downstream consequences on physiology and health. Yet, these findings also suggest that stressors that may be experienced broadly across SES strata (e.g., family conflict), as measured with the LEQ in the current study, may not be the most relevant or deleterious aspects of environmental stress impacting children's health and physiological functioning.…”
Section: Discussionmentioning
confidence: 99%